READING AND COUNTING INTERACTIVE MEDIA FOR CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) - Riza, Lala Septem; Solihat, Syifa; Fitriasari, Novi Sofia; Homdijah, Oom Siti; Nurhayati, Ai Siti; Hidayat, Topik (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Learning for children with autism spectrum disorder (ASD) must specifically cater to their specific characteristics, but learning media specifically tailored for children with ASD is unfortunately still limited. We designed and implemented interactive multimedia adopting the syntax of PECS for reading and counting in children with ASD. Students’ improvement was evaluated after learning and their behavior while learning was documented. Results showed some improvement in students' learning achievement, and all students showed an improvement in terms of behavior when learning.